2016
DOI: 10.15698/mic2016.05.500
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic monitoring identifies phosphatidylthreonine-regulated calcium homeostasis in Toxoplasma gondii

Abstract: Toxoplasma gondii is an obligate intracellular parasite, which inflicts acute as well as chronic infections in a wide range of warm-blooded vertebrates. Our recent work has demonstrated the natural occurrence and autonomous synthesis of an exclusive lipid phosphatidylthreonine in T. gondii. Targeted gene disruption of phosphatidylthreonine synthase impairs the parasite virulence due to unforeseen attenuation of the consecutive events of motility, egress and invasion. However, the underlying basis of such an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…Lytic cycle assays. Standard phenotyping methods were used to determine the impact of genetic manipulation on the lytic cycle of tachyzoites in vitro, as described earlier 10,53 . Plaque assays were performed by infecting confluent HFF cells in 6-well plates (100-200 parasites/well).…”
Section: Functional Expression In Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation
“…Lytic cycle assays. Standard phenotyping methods were used to determine the impact of genetic manipulation on the lytic cycle of tachyzoites in vitro, as described earlier 10,53 . Plaque assays were performed by infecting confluent HFF cells in 6-well plates (100-200 parasites/well).…”
Section: Functional Expression In Escherichia Colimentioning
confidence: 99%
“…In context of this report, we showed that the acute stage of T. gondii can synthesize several major classes of phospholipids, namely phosphatidylcholine (PtdCho), phosphatidylethanolamine (PtdEtn), phosphatidylthreonine (PtdThr), and phosphatidylserine (PtdSer). Among these, PtdThr is an exclusive anionic lipid occurring only in coccidian parasites, which regulates calcium homeostasis in T. gondii 10,11 . PtdThr, PtdCho, and PtdSer are made in the endoplasmic reticulum (ER), whereas PtdEtn is produced at multiple locations including the ER, mitochondrion and parasitophorous vacuole (PV) [3][4][5][6][7][8][9] .…”
mentioning
confidence: 99%
“…However, it was the use of Genetically Encoded Ca 2+ Indicators (GECIs) that provided the final and conclusive evidence that there was a cytosolic Ca 2+ increase right before egress [123]. The use of these indicators has vastly impacted the studies of Ca 2+ in intracellular parasites [95, 117, 123, 127]. Secretion from the micronemes of the perforin-like protein TgPLP1, assists in the permeabilization of the PVM and host cell membrane [128].…”
Section: Microneme Secretion Motility Host Cell Invasion and Egressmentioning
confidence: 99%
“…A pioneering study involving expression of a light-activated adenylate cyclase in the protozoan parasite Toxoplasma gondii has already demonstrated the proof of principle for applying optogenetics in infection research [4]. Equally, expression of gene-encoded biosensors has enabled an otherwise challenging monitoring of subcellular calcium in T. gondii and Plasmodium falciparum enclosed within host cells [8,9]. These works have indeed paved a way to tap the vast potential of optogenetic actuators and biosensors.…”
Section: Light and Seek: A Eukaryote Hiding Within A Eukaryotementioning
confidence: 99%